2010
DOI: 10.1038/ng.624
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies identify IL23R-IL12RB2 and IL10 as Behçet's disease susceptibility loci

Abstract: Behçet's disease is a chronic systemic inflammatory disorder characterized by four major manifestations: recurrent ocular symptoms, oral and genital ulcers and skin lesions. We conducted a genome-wide association study in a Japanese cohort including 612 individuals with Behçet's disease and 740 unaffected individuals (controls). We identified two suggestive associations on chromosomes 1p31.3 (IL23R-IL12RB2, rs12119179, P = 2.7 x 10(-8)) and 1q32.1 (IL10, rs1554286, P = 8.0 x 10(-8)). A meta-analysis of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
365
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 483 publications
(395 citation statements)
references
References 19 publications
18
365
4
8
Order By: Relevance
“…This has already generated tangible benefits, and in BD a recent genome-wide association study (GWAS) has not only confirmed the association with know HLA-B*51 but identified further associations within MHC class I and also an association at IL-10 and IL23R-IL12RB2 loci. 96,97 This is concordant with other smaller candidate single nucleotide polymorphism (SNP) analysis studies that show in sympathetic ophthalmia an association with IL-10-1082 SNP and three haplotype-tagging SNPs(htSNPs) in the IL10 gene, rs6703630, rs2222202, and rs3024490, are significantly associated with susceptibility to non-infectious uveitis, whereas a LTA þ 252AA/ TNFhtSNP2GG haplotype (rs909253 and rs361525) is protective. 98,99 Whether this will predict the outcome on an individual basis is unknown, 100 but it highlights how further GWAS and, more importantly, genomics, RNA sequencing, and transcriptomics, will shape our future approach by identifying new genes, potential biomarkers, and new targets for therapy.…”
Section: How Do We Harness Our Approaches?supporting
confidence: 76%
“…This has already generated tangible benefits, and in BD a recent genome-wide association study (GWAS) has not only confirmed the association with know HLA-B*51 but identified further associations within MHC class I and also an association at IL-10 and IL23R-IL12RB2 loci. 96,97 This is concordant with other smaller candidate single nucleotide polymorphism (SNP) analysis studies that show in sympathetic ophthalmia an association with IL-10-1082 SNP and three haplotype-tagging SNPs(htSNPs) in the IL10 gene, rs6703630, rs2222202, and rs3024490, are significantly associated with susceptibility to non-infectious uveitis, whereas a LTA þ 252AA/ TNFhtSNP2GG haplotype (rs909253 and rs361525) is protective. 98,99 Whether this will predict the outcome on an individual basis is unknown, 100 but it highlights how further GWAS and, more importantly, genomics, RNA sequencing, and transcriptomics, will shape our future approach by identifying new genes, potential biomarkers, and new targets for therapy.…”
Section: How Do We Harness Our Approaches?supporting
confidence: 76%
“…By comparison, B*52/MICA*009 was found in 25% of controls (8). Recently genome-wide association studies (GWASs) in different patient populations showed specific genes linked to BD in different ethnic groups; however, all the studies identified the HLA-B loci as the strongest association (9)(10)(11). However, in a recent study, deep sequencing of the HLA region identified an SNP, rs116799036, close to MICA that gave the strongest association and was independent of HLA-B*51 (12).…”
mentioning
confidence: 99%
“…However, efforts to parse the effects of MICA and HLA-B alleles definitively have been confounded by their particularly strong LD (11)(12)(13)(14). Additionally, HLA-A has been identified as a BD susceptibility locus in numerous studies (2,3,(14)(15)(16)(17), and it has been suggested that HLA-C contributes to BD risk, as well (14).…”
mentioning
confidence: 99%
“…The predominant BD susceptibility locus is the MHC on chromosome 6 (2, 3), which contains the strongest known risk factor for BD, the MHC class I (MHC-I) allele HLA-B*51 (2)(3)(4)(5). Several recent studies have expanded the list of genes or loci implicated in the pathophysiology of BD, which now includes HLA-B, IL10, IL23R, HLA-A, CCR1, STAT4, endoplasmic reticulum amino peptidase 1 (ERAP1), the killer lectinlike receptor cluster on chromosome 12, and, most recently, TLR4 and MEFV (2,3,6,7). Although these genetic studies of BD have provided new clues and insights into the pathogenesis of BD, none has provided a thorough accounting of the individual risk factors within the MHC.…”
mentioning
confidence: 99%